Are Communities Receiving Appropriate Care? : A Study on the Community Health Worker Program in Mozambique - World Bank (World Bank, Washington, DC, 2021)
Community involvement in promoting and providing health services is one of the principles underpinning the Mozambique Health sector strategic plan (2014–2024) and the investment case. Community-based health services in Mozambique are primarily provided through the community health workers or Agentes Polivalentes Elementares (APEs). Existing since 1974, the Ministry of Health (MOH) revitalized its APE program in 2010 after setbacks encountered during the civil war (1976–1992). The revitalized program, led by the Department of Health Promotion under the National Directorate of Public Health, seeks to increase the coverage and the quality of services provided, aiming to train and deploy additional APEs across the country, with a primary role in health promotion and disease prevention and a secondary role in curative services. This study seeks to assess the quality of care (QoC) provided by APEs to inform policymaking for the APE program from an evidence-based perspective.